2015
DOI: 10.1371/journal.pone.0129236
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Leptospirosis: Comparison between Microscopic Agglutination Test, IgM-ELISA and IgM Rapid Immunochromatography Test

Abstract: BackgroundLeptospirosis is diagnosed on clinical grounds, and confirmed by microscopic agglutination test (MAT). IgM-ELISA (Serion-Virion) and immunochromatography test (Leptocheck-WB) are two immunodiagnostic assays for leptospirosis. Their sensitivity, specificity and applicability in Sri Lanka have not been systematically evaluated.MethodsClinically diagnosed leptospirosis patients (n = 919) were recruited from three hospitals in the Western Province of Sri Lanka, during June 2012 to December 2013. MAT, IgM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
122
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(137 citation statements)
references
References 28 publications
6
122
0
3
Order By: Relevance
“…Many published data cited PanBio ELISA to be highly sensitivity in early stages of infection which was in agreement with our study (Panwala et al, 2011;Niloofa, 2015 andZochowski et al, 2001). Certain studies reported a lower rate of sensitivity and specificity (Blacksell et al, 2006 andDesakorn et al, 2012).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Many published data cited PanBio ELISA to be highly sensitivity in early stages of infection which was in agreement with our study (Panwala et al, 2011;Niloofa, 2015 andZochowski et al, 2001). Certain studies reported a lower rate of sensitivity and specificity (Blacksell et al, 2006 andDesakorn et al, 2012).…”
Section: Resultssupporting
confidence: 92%
“…Our study recorded a sensitivity of 75% and specificity of 95% with admission sample for Leptocheck WB in comparison with the reported data (Goris et al, 2013). But some of the earlier reports showed a higher sensitivity and lower specificity rate (Panwala et al, 2011;Panwala Tanvi et al, 2015 andNiloofa et al, 2015).This would be due to geographical distribution of leptospira serovars and time of blood collection.…”
Section: Resultsmentioning
confidence: 92%
“…se realizó mediante la prueba de elisa debido a que esta técnica es sencilla y fácil de ejecutar en condiciones de infraestructura mínima y como una estrategia de tamizaje preliminar de bajo costo. Por otro lado, la complejidad de la prueba mat requiere de un número considerable de serovares y su mantenimiento y la ausencia de laboratorios especializados en la región imposibilitan su uso de rutina y tamizaje [29][30]. Recientemente se están desarrollando estudios para la caracterización molecular de serotipos de aislamientos en Colombia, para establecer un panel diagnóstico más adecuado al contexto epidemiológico del país [31,32].…”
Section: Discussionunclassified
“…La técnica de elisa usada para la detección de anticuerpos IgM contra Leptospira spp. es un método convencional ampliamente usado en el diagnóstico de leptospirosis, por lo tanto, estudios que compararon mat y elisa evidenciaron resultados semejantes en cuanto a su sensibilidad y especificidad [29,30], siendo elisa una prueba de referencia [16]. Los resultados de este estudio indican la presencia de anticuerpos contra Leptospira spp, pero no confirman la infección y, por lo tanto, no constituye evidencia suficiente para emitir un diagnóstico de leptospirosis.…”
Section: Discussionunclassified
“…Usually, the saprophytic strain L. biflexa which shares several surface antigens with pathogenic strains and pathogenic species have also been used [34,44]. The specificity and the sensitivity of these Elisa are quite variable.…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%